(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Lipases are industrially significant enzymes widely used in food, detergent, pharmaceutical, and biodiesel industries. This study investigates the optimization of lipase production by Bacillus subterraneous isolated from abattoir soil in Kurmin mashi Abattoir, Kaduna using agro-allied wastes as substrates in solid-state fermentation (SSF). Soil samples were collected and analyzed to isolate lipase-producing bacteria, which were identified through morphological, biochemical, and molecular techniques. Various agro-wastes such as wheat bran, rice bran, sugarcane peel, and groundnut husk were evaluated for their efficiency in supporting microbial growth and enzyme production. The study aimed to enhance enzyme yield by optimizing key fermentation parameters, including pH, temperature, substrate concentration, incubation time, and agitation speed. The highest lipase activity of 6.90±0.10 U/mL was achieved under optimal conditions: pH 6, temperature 40°C, inoculums level 4.0% (w/v), and incubation time 48 hours. Among the tested agro-allied wastes, groundnut shell and groundnut oil proved to be the most effective substrate for lipase induction. The enzyme was subsequently purified using ammonium sulfate precipitation, dialysis, and gel filtration chromatography. SDS-PAGE analysis confirmed the molecular weight of the purified lipase to be 25kDa. The findings suggest significant industrial potential, particularly in biodegradable detergents, biodiesel production, food processing, and pharmaceutical applications. Moreover, the utilization of agro-waste as a fermentation substrate highlights the economic and environmental sustainability of this production approach, supporting waste valorization and circular bioeconomy models.